Analisis Penyelesaian Konflik Hak Ulayat pada Masyarakat Hukum Adat Di Kabupaten Jayapura Papua - Jordan Randy Zethdan Pellokila (CV. Syntax Corporation Indonesia, 2021)
This research is motivated by the dynamics of economic and infrastructure development in Papua that are increasing. The goal is to realize the welfare of society, while increasing long-standing lags, which in turn raises new problems. Land clearing for plantations and other facilities and infrastructure, intersecting with the interests of indigenous peoples in Papua. The method used in this study is empirical juridical that relies on the results of research in the field. The goal to be obtained is to analyze the resolution of ulayat rights conflicts in indigenous law communities in Jayapura Regency Papua. The results show that land law in Indonesia is inseparable from ulayat rights. Long before the creation of Law No. 5 of 1960 on the Basic Rules of Agrarian Subjects (UUPA), our legal community had known ulayat rights. Conflicts that occur between indigenous law communities and other parties that occur almost throughout Indonesia are one of them due to the uncertainty of the land area of the indigenous law community. The way of settlement that can be taken so far is through litigation efforts, namely through courts and non-litigation dispute resolution efforts outside the court.